The Implementation of Decentralization Policy and the Phenomenon of Local Oligarchy: A Case Study of Public Policy Capture by Local Elites - Siti Marwiyah; Saifuddin Saifuddin; Feris Aldo; Achmad Dany Agustyan; Ayu Ernita (The Future of Education Journal, 2026)
The implementation of decentralization policies in Indonesia following the 1998 Reform Era was intended to bring public services closer to citizens and strengthen local participation in decision-making processes. However, decentralization has also given rise to the phenomenon of local oligarchy, characterized by the concentration of political and economic power in the hands of a small group of regional elites. This study aims to analyze how decentralization creates opportunities for local elites to capture public policy and to identify the factors that facilitate such dominance. The research employs a qualitative approach using a case study method to examine the relationships among political actors, bureaucratic institutions, and economic interest groups in local policymaking processes. The findings reveal that weak institutional accountability, clientelistic practices, and elite control over strategic resources are the primary factors reinforcing local oligarchy. As a consequence, public policies tend to serve elite interests rather than the broader interests of society. Therefore, strengthening transparent, accountable, and participatory governance is essential to reducing elite domination within decentralized political systems. The study highlights the need for institutional reforms that promote democratic governance and ensure that public policy remains responsive to citizens’ needs and aspirations.